P5P2RA-Based Digital Comics as Character Education Media: A Qualitative Study on Supporting the Kurikulum Cinta and Preventing Bullying in Madrasah Ibtidaiyah - Hidayati, Fithriyah Nurul; Fatmawati, Nor Laili (CV. Media Digital Publikasi Indonesia, 2026)
The rise of bullying cases in primary education underscores the urgent need for effective character education media that are engaging, contextual, and value-oriented. In response, the Indonesian Ministry of Religious Affairs has recently introduced the Kurikulum Cinta, which emphasizes compassion, empathy, inclusivity, and non-violence, particularly within Madrasah Ibtidaiyah. As a newly implemented curriculum, its practical application remains limited and underexplored, especially in terms of instructional media. This qualitative study investigates the use of P5P2RA-based digital comics as character education media to support the Kurikulum Cinta and prevent bullying in Madrasah Ibtidaiyah. The research involved teachers and students from three madrasahs in Madura, Indonesia. Data were collected through classroom observations, in-depth interviews, and documentation analysis, and were analyzed thematically. The findings reveal that P5P2RA-based digital comics effectively promote empathy, mutual respect, cooperation, and anti-bullying attitudes among students. The study highlights how narrative-based digital media can translate abstract curriculum values into meaningful learning experiences. This research contributes empirical evidence to support the implementation of the Kurikulum Cinta and enriches scholarly discourse on innovative character education practices in Islamic primary education.